2000
DOI: 10.1088/0031-9155/45/8/313
|View full text |Cite
|
Sign up to set email alerts
|

Home radon levels and seasonal correction factors for the Isle of Man

Abstract: Ionizing radiation dose levels due to home radon can rise to levels that would be illegal for workers in the nuclear industry. It is well known that radon levels within homes and from home to home, and also from month to month, vary considerably. To define an Isle of Man radon seasonal correction factor, readings were taken in eight homes over a 12 month period. An average island indoor exposure of 48 Bq m(-3) (range 4-518 Bq m(-3)) was determined from 285 homes selected from a cohort of 1300 families particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…The underlying geology of this region differs to that of many other parts of the UK, large areas being immediately underlain by large granite bodies. Grainger et al (2000) suggested that as the UK seasonal correction factors had been derived from the mainland UK database, which is dependent on UK geology, seasonal correction factors may need to be different for the Isle of Man, which has a very different geology in many ways. Grainger et al (2000) measured radon levels following NRPB protocols in homes of over 400 families for a period of 3 months in the winter.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The underlying geology of this region differs to that of many other parts of the UK, large areas being immediately underlain by large granite bodies. Grainger et al (2000) suggested that as the UK seasonal correction factors had been derived from the mainland UK database, which is dependent on UK geology, seasonal correction factors may need to be different for the Isle of Man, which has a very different geology in many ways. Grainger et al (2000) measured radon levels following NRPB protocols in homes of over 400 families for a period of 3 months in the winter.…”
Section: Discussionmentioning
confidence: 99%
“…Grainger et al (2000) suggested that as the UK seasonal correction factors had been derived from the mainland UK database, which is dependent on UK geology, seasonal correction factors may need to be different for the Isle of Man, which has a very different geology in many ways. Grainger et al (2000) measured radon levels following NRPB protocols in homes of over 400 families for a period of 3 months in the winter. They also measured seasonal variation for 12 months in 10 homes and, from this, a seasonal correction factor was derived by dividing the arithmetic mean for each time period by the annual arithmetic mean.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations